The systemic influence of chronic smoking on skin structure and mechanical function. Issue 4 (19th June 2020) - Langton, Abigail K; Tsoureli‐Nikita, Evridiki; Merrick, Holly; Zhao, Xuegen; Antoniou, Christina; Stratigos, Alexander; Akhtar, Riaz; Derby, Brian; Sherratt, Michael J; Watson, Rachel EB; Griffiths, Christopher EM
Abstract: One of the major functions of human skin is to provide protection from the environment. Although we cannot entirely avoid, for example, sun exposure, it is likely that exposure to other environmental factors could affect cutaneous function. A number of studies have identified smoking as one such factor that leads to both facial wrinkle formation and a decline in skin function. In addition to the direct physical effects of tobacco smoke on skin, its inhalation has additional profound systemic effects for the smoker. The adverse effects on the respiratory and cardiovascular systems from smoking are well known. Central to the pathological changes associated with smoking is the elastic fibre, a key component of the extracellular matrices of lungs. In this study we examined the systemic effect of chronic smoking (>40 cigarettes/day; >5 years) on the histology of the cutaneous elastic fibre system, the nanostructure and mechanics of one of its key components, the fibrillin‐rich microfibril, and the micromechanical stiffness of the dermis and epidermis. We show that photoprotected skin of chronic smokers exhibits significant remodelling of the elastic fibre network (both elastin and fibrillin‐rich microfibrils) as compared to the skin of age‐ and sex‐matched non‐smokers. This remodelling is not associated with increased gelatinase activity (as identified by in situ zymography). Histological remodelling is accompanied by significant ultrastructural changes to extracted fibrillin‐rich microfibrils. Finally, using scanning acoustic microscopy, we demonstrated that chronic smoking significantly increases the stiffness of both the dermis and the epidermis. Taken together, these data suggest an unappreciated systemic effect of chronic inhalation of tobacco smoke on the cutaneous elastic fibre network. Such changes may in part underlie the skin wrinkling and loss of skin elasticity associated with smoking. © 2020 The Authors. The Journal of Pathology published by John Wiley & Sons Ltd on behalf of Pathological Society of Great Britain and Ireland.